Identification of Region-Specific Cytoskeletal and Molecular Alterations in Astrocytes of Mecp2 Deficient Animals - Albizzati, Elena; Florio, Elena; Miramondi, Federica; Sormonta, Irene; Landsberger, Nicoletta; Frasca, Angelisa (Frontiers in Neuroscience, 2022)
Rett syndrome (RTT) is a neurodevelopmental disorder that represents the most common genetic cause of severe intellectual disability in females. Most patients carry mutations in the X-linked MECP2 gene, coding for the methyl-CpG-binding protein 2 (MeCP2), originally isolated as an epigenetic transcriptional factor able to bind methylated DNA and repress transcription. Recent data implicated a role for glia in RTT, showing that astrocytes express Mecp2 and that its deficiency affects their ability to support neuronal maturation by non-cell autonomous mechanisms. To date, some molecular, structural and functional alterations have been attributed to Mecp2 null astrocytes, but how they evolve over time and whether they follow a spatial heterogeneity are two aspects which deserve further investigations. In this study, we assessed cytoskeletal features of astrocytes in Mecp2 deficient brains by analysing their arbour complexity and processes in reconstructed GFAP+ cells at different ages, corresponding to peculiar stages of the disorder, and in different cerebral regions (motor and somatosensory cortices and CA1 layer of hippocampus). Our findings demonstrate the presence of defects in Mecp2 null astrocytes that worsen along disease progression and strictly depend on the brain area, highlighting motor and somatosensory cortices as the most affected regions. Of relevance, astrocyte cytoskeleton is impaired also in the somatosensory cortex of symptomatic heterozygous animals, with Mecp2+ astrocytes showing slightly more pronounced defects with respect to the Mecp2 null cells, emphasising the importance of non-cell autonomous effects. We reported a temporal correlation between the progressive thinning of layer I and the atrophy of astrocytes, suggesting that their cytoskeletal dysfunctions might contribute to cortical defects. Considering the reciprocal link between morphology and function in astrocytes, we analysed the effect of Mecp2 deficiency on the expression of selected astrocyte-enriched genes, which describe typical astrocytic features. qRT-PCR data corroborated our results, reporting an overall decrement of gene expression, which is area and age-dependent. In conclusion, our data show that Mecp2 deficiency causes structural and molecular alterations in astrocytes, which progress along with the severity of symptoms and diversely occur in the different cerebral regions, highlighting the importance of considering heterogeneity when studying astrocytes in RTT.